Device to predict pelvic floor integrity during vaginal delivery: an intra- and interrater reliability study of the Epi-no distensibility measurement. (2nd November 2021) - Paschoal, Aline; Uchiyama Nakamara, Mary; Araujo Júnior, Edward; Petricelli, Carla Dellabarba; Alexandre, Sandra Maria; Zanetti, Miriam Raquel Diniz
Abstract: Objective: To determine the test–retest reliability of the pelvic floor distensibility evaluation with Epi-no ® device. Methods: Prospective, blinded observational study with 32 women pregnant from 35 gestational weeks. An Epi-no ® balloon was inflated within the pregnant woman's vagina and the maximum circumference achieved was measured using a standard metric measuring tape. Measurements were performed twice in a day by two physiotherapists in a randomized order. Intraobserver reproducibility was obtained with another evaluation 7–14 d after the initial examination. The intraclass correlation coefficient (ICC) was used to determine the intra and interrater reliability and the respective 95% confidence intervals with an alpha level of 0.05. Results: From a total of 32 included pregnant women, 28 were analyzed; they were 29.3 (±5.97) years old, were at 37 (±1.3) weeks' gestation and presented a mean Epi-no ® circumference of 20.4 (±2.4) cm. Regarding the intraobserver analysis, examiner 1 observed a maximum circumference of 20.6 (±2.6) cm in the first evaluation and 20.2 (±2.4) cm in the second evaluation, with good reliability (ICC = 0.85). Examiner 2 observed 19.7 (±2.4) cm in the first evaluation and 21.0 (±2.0) cm in the second one, with moderate reliability (ICC = 0.58). Regarding the interobserver analysis, there was good reliability on two evaluation days, with an ICC of 0.76 and 0.82, respectively. Conclusions: Epi-no ® device is a reliable device for physiotherapists to measure pelvic floor distention during pregnancy.